Respuesta :

Answer:

The 2 values that makes the function equal to 18 is 3 and -6

Step-by-step explanation:

First you can convert the quadratic equation from standard form to root form

Step 1: Substitute f(g) = 18

Step 2: Move 18 to the other side to create

0 = g² + 3g - 18

Step 3: Now we rearrange equation from standard form into root form

Step 4: Find what adds to 3 and multiples to -18

-3 and 6 adds to 3 and multiples to -18

Step 5: Now we substitute -3 and 6 into the root equation

0 = (g-3)(g+6)

Step 6: Set the brackets to 0 and solve

g - 3 = 0

g = 3

g + 6 = 0

g = -6